An optimized cultivation method for future in vivo application of γδ T cells - Bold, Anna; Gross, Heike; Holzmann, Elisabeth; Knop, Stefan; Hoeres, Timm; Wilhelm, Martin (Frontiers in Immunology, 2023)
γδ T cells, with their properties of both the innate and acquired immune systems, are suitable candidates for cellular immunotherapy in cancer. Because of their non-major histocompatibility complex (MHC) binding T cell receptor, allogenic transfer is feasible without relevant graft versus host reactions. In recent years, much experience has been gained with ex vivo expansion and stimulation of γδ T cells using bisphosphonates and Interleukin 2. Unfortunately, many current stimulation protocols are based on the use of xenogeneic materials and other potentially hazardous supplements, which conflicts with basic principles of Good Manufacturing Practice (GMP). Adherence to the concept and current guidelines of GMP is state of the art for production of Advanced Therapy Medicinal Products (ATMP) like cell therapeutics and a necessity for clinical use under a regulatory perspective. In this study, we developed a new stimulation protocol that induces a marked increase of γδ T cells counts and allows for an easier transition from research to clinical applications with minimized regulatory workload. It reliably leads to a cell product with a purity of more than 90% γδ T cells and improved in vitro anti-tumor activity compared to our previous standard procedure. Furthermore, by investigating correlations between properties of unstimulated γδ T cells and proliferation rate as well as degranulation ability of stimulated γδ T cells, we can draw conclusions about suitable donors. Finally, we examined if expansion can be improved by pulsing zoledronate and/or using Interleukin 15 with or without Interleukin 2. Significant improvements can be achieved with respect to intrinsic and antibody-dependent cell-mediated cytotoxicity. Our results demonstrate that the stimulation protocol presented here leads to an improved γδ T cell product for future clinical applications.